Effect of Foliar Boron Sprays on Yield and Fruit Quality of Citrus - Karim, Mohammad R. (College of Agriculture, University of Arizona (Tucson, AZ), 1996)
Deficiency of boron (B) in citrus has serious consequences for tree health and crop production. There is evidence that B deficiency may be a problem in Arizona citrus. Certainly, many symptoms of B deficiency are apparent, especially on the Yuma Mesa. A field trial was conducted at Yuma, Arizona to examine the effect of foliar boron application on fruit yield and quality of Citrus sinensis and C. limon. Boron was applied to 5 year old Citrus sinensis cv. Hamlin and C. limon cv. Rosenberger Lisbon trees at 5 different concentrations (0 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm) either before flowering or after flowering. At harvest, fruit yield and quality, and boron concentrations were determined. Foliar application appeared to increase leaf boron concentration (r= 0.50, p= 0.004). Fruit set was increased in Hamlin trees receiving bloom and post bloom applications of boron at the 1000 ppm level. Boron applications had no significant effect on lemon yield in these studies. This fruit set increase in Hamlin accounted for a 35% increase in overall yield relative to control trees. However, there was no significant difference in fruit weight, fruit pH, titratable acidity, peel thickness, juice volume, or soluble solid content of the fruits among treatments. Previous studies indicate that boron influenced in vivo and in vitro pollen germination in many crops. A plausible explanation for increased fruit yield may be that the applied boron was transported to the flowers where it exerted its influence of increased fruit set through an effect on pollen viability and/or pollen tube growth. However, clearly boron supplementation must be performed judiciously to avoid fruit drop from over -application of the element.